Konsumsi Seng (Zn) dan Zat Besi (Fe) dan Kadar Hemogoblin Pada Siswi SMA Negeri 1 Gianyar - Indraswari, Dewa Ayu Ratri; Padmiari, Ida Ayu Eka; Suarjana, I Made (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Young women are susceptible to nutritional problems, one of which is anemia. The cause of anemia is the lack of consumption of macro and micronutrients, such as iron and zinc. The problem of anemia in adolescent girls will cause adverse effects such as causing babies born with low weight, stunting babies, and high prenatal mortality. The purpose of this study was to determine the relationship between zinc and iron consumption and hemoglobin levels in high school students Negeri 1 Gianyar. The type of data in this study is analytical using a cross sectional design. The population in this study was grade 11 and 12 students with a sample of 60 people selected by random sampling. Data on zinc and iron consumption were obtained using a 24-hour food recall questionnaire processed using the 2007 Nutri Survey program, and hemoglobin levels were obtained by digital multicheck method, namely with GCHb Easy Touch. Data were analyzed using bivariate analysis using the spearman rank test. The results showed the level of zinc and iron consumption was still lacking. The average consumption of zinc and iron after the data was processed was zinc consumption which was 4.3 mg and iron consumption which was 3.95 mg. Consumption of zinc and iron is lower than the daily needs, namely zinc 9 mg and iron 15 mg. There was no significant association (p0.05) between zinc consumption and hemoglobin levels. TThere was no significant association (p0.05) between iron and hemoglobin levels in adolescent girls.